The AJ517 antibody labels the mouse CD8β protein by western blot - Ameti, Ilhan; Sassi, Ali; Bulla, Monica; Manoukian, Arec; Giusti, Teresa; Gaspoz, Vincent; Spedaliero, Sébastien; Maxit, Orlane; Hussami, Sara; Guilhen, Cyril (Antibody Reports, 2020)
The AJ517 antibody detects the mouse CD8β protein by western blot.